2011
DOI: 10.1126/science.1197738
|View full text |Cite
|
Sign up to set email alerts
|

The Origins of Hot Plasma in the Solar Corona

Abstract: The Sun's outer atmosphere, or corona, is heated to millions of degrees, considerably hotter than its surface or photosphere. Explanations for this enigma typically invoke the deposition in the corona of nonthermal energy generated by magnetoconvection. However, the coronal heating mechanism remains unknown. We used observations from the Solar Dynamics Observatory and the Hinode solar physics mission to reveal a ubiquitous coronal mass supply in which chromospheric plasma in fountainlike jets or spicules is ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
289
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(322 citation statements)
references
References 26 publications
22
289
2
3
Order By: Relevance
“…It is therefore plausible that the few brightenings in the AIA 304, 171, and 211 Å bands that we and De Pontieu et al (2011) observe near the footpoint of active region loops are signatures of upflowing chromospheric material heated to transition-region temperatures, up to 0.5 MK, although the EIS observations presented here cannot rule out heating to even higher temperatures.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…It is therefore plausible that the few brightenings in the AIA 304, 171, and 211 Å bands that we and De Pontieu et al (2011) observe near the footpoint of active region loops are signatures of upflowing chromospheric material heated to transition-region temperatures, up to 0.5 MK, although the EIS observations presented here cannot rule out heating to even higher temperatures.…”
Section: Discussionmentioning
confidence: 52%
“…The contribution of cool (log T [K] < 5.7) plasma to the 171 Å channel is also clearly significant. Our results suggest that the interpretation given by De Pontieu et al (2011) of the AIA 171 Å and 211 Å observations near active region loop footpoints should be treated with extreme caution. Indeed we have shown that for both a loop footpoint and a loop leg region, the contribution of "cool" (log T [K] < 5.7) plasma is large.…”
Section: Discussionmentioning
confidence: 67%
“…That in SUMER spectra no EEs are observed in coronal lines -besides the fact that no really good coronal lines for disk observations exist in the SUMER wavelength range -does not contradict the scenario suggested by De Pontieu et al (2011), who found that the heated volume is outside the leading edge of the jet. If heating takes place while the jet propagates and expands, then spectrometers, in particular slow spectrometers, will have difficulties to observe this heating process.…”
Section: Discussionmentioning
confidence: 64%
“…These candidates could be type II spicules or rapid blueshifted events (RBEs; De Pontieu et al , 2011McIntosh et al 2009; Rouppe van der Voort 2009) because they have very similar characteristics in terms of velocity, lifetime, size, and repeatability. A direct proof of helicity in RBEs through imaging instruments has to our knowledge not been reported yet and may be difficult to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…The large spatial superposition of spicules, particularly at the limb, makes it challenging to track every individual spicule (e.g., see "Selection Effects and Errors" in Pereira et al 2012). Spicules also recur frequently from the same footpoint region (Beckers 1968;Suematsu et al 1995;De Pontieu et al 2011;Pereira et al 2012;Sekse et al 2013b;Yurchyshyn et al 2013), meaning that when a particular spicule disappears it can be quickly replaced by another of similar intensity in the same place. Judge et al (2012;hereafter JCR12) study disk spicules at a wavelength of Hα + 0.11 nm, and find spicules that appear and disappear suddenly over several Mm.…”
Section: Appearance and Disappearancementioning
confidence: 99%